Radiometric Mapping for Naturally Occurring Radioactive Materials (NORM) Assessment in Mamuju, West Sulawesi - H. Syaeful; I.G. Sukadana; A. Sumaryanto (Atom Indonesia, 2014)
Mamuju has been known to have high radiation dose rate which is comes from NORM in rock and soil. Major concern is due to its location which is near inhabitant settlement area. Preliminary research has been done by environmental team which is limited to main access road only, while some remote area has left untouched. The purpose of the research is to delineate the location and distribution of thorium and uranium anomaly in Mamuju, and also to provide adequate information regarding the anomaly and high dose rate area to decision makers and stakeholders in neither local nor central government. Method applied is radiometric mapping using spectrometer RS-125 with NaI(Tl) detector in the area of interest Geological Formation of Adang Volcanic, which is more than 800 square km in size. The radiometric mapping method is widely used in uranium/thorium exploration, and now has been added with the measurement of radiation dose rate which is appropriate to environmental surveys. The mapping has been successfully delineated the area of NORM or the area with thorium and uranium anomaly. Thorium and uranium anomaly identified related with multi-geological-process resulting the increase of grade into several fold from its original state.Received: 08 November 2013; Revised: 20 February 2014; Accepted: 10 March 2014